Pengembangan Paket Wisata Di Kota Ternate - Karim, Taufik Z.; Hasyim, Abdul Wahid; Meidiana, Christia (Jurnal Tata Kota dan Daerah, 2014)
In the current era of regional autonomy, tourism is one of the key sectors of a region’s economy development, as each local government is required to develop and to utilize its natural resources, namely tourism sector, in order to increase its local revenue to improve the welfare of its society. Despite having diverse tourism attraction potentials including historical, cultural, natural, and artificial tourist attractions, the city of Ternate has not developed its potential prevalently. The purpose of this study is therefore to identify potential tourist attraction, to arrange clusters of the potentials based on their common attraction characteristics, and to develop a tourism package formulation strategy in Ternate. The analytical methods used were descriptive analysis on the characteristics of Ternate’s tourism potential, and quantitative analysis including cluster analysis to arrange tourism clusters, travel time analysis, and tour package price calculations. The results showed that the tourism attractions in Ternate could be classified into three different clusters based on their shared values. The first cluster consists of palace of Sultan of Ternate, Sulamadaha Beach, BobaneIci, Legu Gam Festival, and the Festival of Kora-kora. Cluster II includes Oranje Fort, Kalamata Fort, St. Paulo Fort, Tolucco Fort, St W Church, ThianHou Temple King, Resident Bridge, Grave of Sultan Badaruddin II, Batu Angus, Tolire Lake, and Laguna Lake. Finally, Cluster III includes Kastela Fort, Grave of Sultan Babullah, KedatonIci, Kastela Beach, Tabanga Beach, Ake Rica, CengkehAfo, and Gamalama Tracking. Moreover, the study proposed three tour packages: two recreational and cultural package and one cultural and adventural package. Keywords: tour route, tour packages, analysis cluster